Inside Assessment Practices: Exploring Perspectives of Vocational High School Teachers - Agus Supriyadi (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
This study delves into the assessment practices of vocational high school language teachers, aiming to gain insights into their perspectives on evaluating student learning outcomes. The research design encompasses both qualitative and quantitative approaches, focusing on teachers of Bahasa Indonesia and English language subjects in SMK Negeri 10 Malang. Data collection involved interviews and document analysis, providing a comprehensive understanding of teachers' understanding and implementation of assessment concepts. The findings reveal that a significant portion, approximately 25% of teachers, possess a solid grasp of assessment principles and effectively apply them in practice. However, it is evident that many teachers struggle to utilize a variety of assessment techniques to evaluate and assess student learning outcomes accurately. The study highlights the need for professional development initiatives that address these gaps in understanding and provide guidance on effective assessment practices. By shedding light on vocational high school English teachers' perspectives and practices related to assessment, this research contributes to the broader discourse on improving assessment methodologies in language education.